Falcon brigade combat and command in Somalia and Haiti - Casper, Lawrence E. (Lynne Rienner, 2001)
"Col. Lawrence E. Casper (U.S. Army, Ret) narrates the first documented account by a military officer of the harrowing U.S. operations in Somalia and Haiti." "As commander of the Falcon Brigade, 10th Mountain Division, and the UN Quick Reaction Force (QRF), Casper experienced Operation Continue Hope firsthand. Falcon Brigade and Special Operations aviators shared the skies over Mogadishu on October 3, 1993, providing cover as the QRF fought block by block to reach the stranded troops and remove them to safety. Casper's candid account of Operation Continue Hope and the brigade's involvement in Somalia, showcases the leadership skills and courage necessary for troop survival under beleaguered circumstances." "Just six months after their return from Somalia, Casper and the Falcon Brigade were on the flight deck of the nuclear aircraft carrier USS Eisenhower, preparing to air-assault 10th Mountain Division Lightfighters onto the shores of Haiti during Operation Uphold Democracy. Casper brings to life the frustrations and challenges the brigade soldiers experienced as they worked around the clock for thirty days, and he captures the untiring cooperation between soldiers and sailors as they joined together to ensure the success of the operation. His account concludes with the brigade's subsequent four-month involvement in Haiti." "Not only a telling and vivid history, Falcon Brigade is an insightful - and rare - discussion of what did and did not work, and what went on behind the scenes at the operational level."